‘MISTERI TIDUR’ ….. OR….. WHAT IS SLEEP? - Anton Coenen (MANASA, 2012)
An overview on the topic of sleep is presented. Two assumed functions of sleep are highlighted: the restorative hypothesis, implying that (deep) sleep is involved in body restoration, and the information processing hypothesis, saying that sleep plays a role in memory consolidation. The structure of sleep, with its three main characteristics (deep sleep occurring in the first part of the night and light sleep in the second part, while REM sleep appears in cyclical phases during the entire bedtime) is described. Detailed information is provided for REM sleep, given its strict relationship with dreaming, a still enigmatic process. It is emphasized that sleep is a circadian rhythm, coupled to the light-dark and the body temperature cycles. The length of the nightly sleep in relation to healthiness is discussed, as well as the cognitive capabilities of a sleeping brain. Poor sleep and sleep disorders are frequently occurring phenomena whereas the cause of psychophysiological insomnia is also indicated. Snoring and the relation with sleeping postures pass in review, as well the disorder of sleep apnoea. A description isgiven of CPAP, an efficient treatment for sleep apnoea. This sleep review is closed by the sickness narcolepsy, whereby (REM) sleep irresistible intrudes in waking life.